Male Infertility As A Bad News: A Review - Fahmi Bahar (Journal of Global Pharma Technology, 2019)
Having children is a dream for every married couple. However, this process is not that easy for 15% couples worldwide who suffer infertility. Infertility is the failure to achieve a clinical pregnancy after twelve months of regular and unprotected intercourse. Half of infertility causes come from the man called male infertility. Male factors of infertility vary greatly from mild one like oligozoospermia to severe one like extreme oligozoospermia which make the natural pregnancy difficult to happen, hence a help from assisted reproductive technology is needed. In more extreme case like testicular agenesis, having children really becomes a necessity and it will bring bad news to him. Bad News (BN) refers to a condition of hopelessness, threatening life and body or anything which raises the patients’ anxiety about his future. In this case, male infertility can be categorized as BN since it causes loss of hope and anxiety. The process of Breaking Bad News (BBN) requires good communication skill. There were several BBN protocols formulated previously covering Advance preparation, Build relationships, Communicate well, Deal with the patient, Encourage emotion (ABCDE), Background, Rapport, Explore, Announce, Kindling, Summarize (BREAKS) and Settings, Perception, Invitation, Knowledge, Empathy, Strategy (SPIKES). Each protocol had been applied to other medical fields such as oncology, pediatric etc. Whilst its application on male infertility cases has never been published. Even if this protocol is able to be applied properly, it is capable to increase the patients’ knowledge, improve their psychological condition and maintain the threshold of hope for having children.Keywords: Male Infertility, Communication, Bad News, Breaking Bad News